2016
DOI: 10.1111/bph.13470
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effects of sinomenine in a rat model of postoperative pain

Abstract: BACKGROUND AND PURPOSEThis study examined the antinociceptive effects of sinomenine in a rat model of postoperative pain. EXPERIMENTAL APPROACHMale and female rats were subjected to a surgical incision in the right hind paw, and the von Frey filament test was used to measure mechanical hypersensitivity after drug or vehicle treatment (p.o. or i.p.). Rats were treated daily with sinomenine before or after the surgery and the AUCs of the antinociceptive effects measured during a 4 h period were calculated to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 29 publications
(45 reference statements)
1
23
0
Order By: Relevance
“…Previous studies by others and us showed that sinomenine exhibited antinociceptive effect in a wide range of rat and mice models (Gao et al, 2013a;Rao et al, 2017;Zhu et al, 2016;. Work presented in this thesis expanded these results by showing that repeated administration of sinomenine produced persistent effects in rat and mice models of neuropathic pain with signs of tolerance.…”
Section: Repeated Sinomenine Administration Alleviates Chronic Neuropsupporting
confidence: 57%
“…Previous studies by others and us showed that sinomenine exhibited antinociceptive effect in a wide range of rat and mice models (Gao et al, 2013a;Rao et al, 2017;Zhu et al, 2016;. Work presented in this thesis expanded these results by showing that repeated administration of sinomenine produced persistent effects in rat and mice models of neuropathic pain with signs of tolerance.…”
Section: Repeated Sinomenine Administration Alleviates Chronic Neuropsupporting
confidence: 57%
“…The threshold for tactile allodynia was measured with a series of von Frey filaments (von Frey Filaments; Bioseb, Vitrolles, France), ranging from 2.44 to 5.88 (0.03 -60.0 g), according to the methods of Park et al [28] and Zhu et al [29].…”
Section: Von Frey Testmentioning
confidence: 99%
“…Sinomenine is a morphinan derivative extracted from the traditional Chinese medicine Sinomenium acutum. 9 It has been shown to possess a variety of pharmacological effects, such as anti-inflammatory, anti-angiogenesis, antiarrhythmic, and immunosuppressive properties. 10 13 A large number of preclinical and clinical studies have confirmed that sinomenine is effectively against rheumatoid arthritis, arrhythmia, and glomerular diseases.…”
Section: Introductionmentioning
confidence: 99%